A DEM based investigation of mass movement sediment delivery : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Soil Science, Massey University - Lovell, Leyton Richard (Massey University, 1998)
Environmental legislation in New Zealand has required local and regional government to place a greater emphasis upon the external effects of land use. For New Zealand hill country this means a quantitative understanding of accelerated soil erosion in terms of its effects upon downstream sedimentation and subsequent flood events. This study was an investigation into the spatial distribution of soil slip erosion (NZLRI) for the Waipaoa River Catchment (~2204km2), East Cape, New Zealand. A combined Remote Sensing and GIS approach using orthorectified aerial photographs and digital elevation models was employed to investigate the topographic attributes influencing the spatial pattern of erosion, utilising a series of classified erosion maps. Of the variables examined, slope, aspect, elevation, and the soil moisture index (SMI) were quantitatively reaffirmed as controlling influences upon mass movement. The erosion maps in conjunction with hydrological flow accumulation images were also found to objectively determine thresholds for identifying stream channel networks from the DEM. The erosion maps when combined with historical data were used to construct sediment delivery ratios and sediment budgets for each landsystem investigated. The most significant influences upon landsliding were combined in a data driven model to assign a probability of landsliding for each pixel, which can later be used to create landslide susceptibility maps and assist in the allocation of soil conservation resources. Keywords: ORTHORECTIFIED AERIAL PHOTOGRAPHS, DEMs, SOIL SLIP EROSION, SEDIMENT DELIVERY RATIOS, SEDIMENT BUDGETS
Keywords: New Zealand; Gisborne District; Waipaoa River Catchment; Waipaoa River Watershed; Sediment transport; Soil erosion; DEMs; Soil slip erosion; Orthorectified aerial photographs; Sediment delivery ratios; Sediment budgets